Immune checkpoint inhibitors-associated vasculitis: a heterogeneous condition with possible severe disease course - Chanson, Noémie; Galvagni, Alexandre; Ramos-Casals, Manuel; Ruiz, Juan Ignacio; Suijkerbuijk, Karijn P. M.; Gente, Karolina; Kerschen, Philippe; Karam, Jean Denis; Belkhir, Rakiba; Outh, Rodereau; Closs-Prophette, Fabienne; Morillo, Jose Salvador Garcia; et al. (Rheumatology, 2025)
Objective To describe presentation, treatment and outcome of immune checkpoint inhibitor (ICI) associated-vasculitis in cancer patients in a multicentre study.Methods Thanks to the ImmunoCancer International Registry (ICIR), a multidisciplinary network focused on the research of the immune related adverse events related to cancer immunotherapies, patients presenting with a clinical and/or radiological suspicion of vasculitis and histological evidence of vasculitis after being exposed to ICIs were retrospectively identified.Results Twenty-eight cases were identified in the ICIR registry. The median interval between starting ICI treatment and vasculitis diagnosis was 4 months. Small vessel vasculitis was predominant (n = 21), followed by large vessel (n = 4) and medium vessel (n = 3). The small vessel vasculitis included 10 unclassified vasculitis either with limited cutaneous involvement (n = 6) or systemic involvement (n = 4), five IgA vasculitis, three cryoglobulinemic vasculitis, and three ANCA+ vasculitis. At presentation or during the evolution, renal and neurologic manifestations were evidenced in seven cases each (25%). Renal biopsies documented immune glomerulopathies in six cases. Only seven patients (25%) fulfilled the 2022 ACR/EULAR classification criteria (four giant cell arteritis, two EGPA and one GPA). Most patients (90%) required systemic corticosteroid and an additional drug was given in 10 patients (36%). Vasculitis outcome was good: 22 patients had vasculitis complete response, no patient died due to vasculitis. Nine patients (32%) were rechallenged with immunotherapy with only one relapse.Conclusion ICI-associated vasculitis are rare, heterogeneous, but can be severe requiring urgent multidisciplinary management with aggressive treatment.